Unveiling the Synergy: Imc Strategies and Success of Catacomb Props Maker in Magetan for International Markets - Azalea Abril HERMANTO; Monika TEGUH (International Journal of Environmental, Sustainability, and Social Science, 2024)
This quasi-qualitative research delves into the world of Catacomb Props, a unique Star Wars property maker in Indonesia's Magetan region. Despite being the sole business of its kind in the country, the owners recognize the need for effective marketing strategies due to fluctuating sales. The study aims to evaluate the implementation of Integrated Marketing Communication (IMC) strategies in enhancing Catacomb's sales. Conducted through in-depth interviews, and documentation, the research focuses on the Maron Hamlet, Banyu Putih, Buluharjo Village, Plaosan District, Magetan Regency. Analyzing the period from 2017 to 2023, the research sheds light on the efficacy of IMC for Catacomb Props. This abstract succinctly outlines the research's objectives, methodology, key findings, and offers a brief interpretation of the results and conclusions, adhering to a clear and concise format.